1965
DOI: 10.1002/pssb.19650110239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen on Some Electrical Properties of Selenium

Abstract: It is established several, previously obscure, properties of selenium are due t o the presence of oxygen and to oxygen complex formation. The properties include the appearance of an extremum in the curves of the concentration dependence of electroconductivity (a), thermoelectromotive force (0), thermal conductivity (A), density (e), mechanical strength, activation energy during self diffusion ( A E ) , and microhardness ( H ) . Other properties are the shift of the second maximum in the photoconductivity curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…The values of Mott's parameters W and aR are of the order of the few k B T and greater than unity, respectively. This shows a close agreement with Mott's VRH [30,35,36].…”
Section: Temperature Effectsupporting
confidence: 87%
“…The values of Mott's parameters W and aR are of the order of the few k B T and greater than unity, respectively. This shows a close agreement with Mott's VRH [30,35,36].…”
Section: Temperature Effectsupporting
confidence: 87%
“…This difference may be due to differences in morphology where all samples have polycrystalline nature except the complete amorphous nature recorded for the sample (Se 60 Te 40 ) 80 Tl 20 as confirmed by XRD. The expression of σ 0 obtained by various authors is given by: σ0=e2ν02[N(Ef)8παkBT]1/2, where ν 0 is the Debye frequency (10 13 Hz). The hopping distance, R , and hopping energy, W , are given by: R=[98παkBTN(Ef)]1/4, W=34πR3Ntrue(Eftrue). …”
Section: Resultsmentioning
confidence: 99%
“…To find out the type of charge carriers majority and calculate its density and its mobility of films (As0.5Se0.5 doped with Te at 1%) has been used Hall measurements technique as shown in Fig. (4) after placing the films perpendicular to the magnetic field (Bz) when changing the current (IX) through the films recorded change in Hall voltage (VH) when calculation the straight mail graphs of the relationship between that shape (IX) and (VH) the Hall coefficient was found (RH), it was found that the relationship between (IX) and (VH) was positive, i.e. the films (As0.5Se0.5 doped with 1%Te) deposited at room temperature and annealed at (T a = 348,398 and 448)K is the kind of (ptype), this result is consistent with (Mahan and Bube) [9]and (Khan and Adler) [11], (C. Chen) [13].…”
Section: Hall Effectmentioning
confidence: 99%
“…Recently, the investigation of electron transport in disordered system has gradually been developed and the investigation of gap states is of particular interest because of their effect on the electrical properties of semiconductors [2]. The effect of impurity in an amorphous semiconductor may be widely different, depending upon the conduction mechanism and the structure of the material while in crystalline semiconductors the effect of a suitable impurity is always to provide a new donor and or acceptor states, this is not essential in amorphous semiconductor [3,4]. The exposing process of film to a certain temperature in a specific period of time called the annealing has been carried out either in vacuum or in presence of a particular gas or in air.…”
Section: Introductionmentioning
confidence: 99%